2013
DOI: 10.2217/dmt.12.62
|View full text |Cite
|
Sign up to set email alerts
|

Problems associated with diabetes care in India

Abstract: More than 61 million people with diabetes live in India, a country that is already facing challenges such as malnutrition, poverty and socioeconomic burden caused by communicable diseases. The main reasons for the ever-increasing diabetes epidemic are population growth, urbanization, unhealthy food habits, obesity and lack of physical activity. Diabetes also causes other complications, including cardiovascular disorders, diabetic retinopathy, diabetic nephropathy and peripheral neuropathy, which are responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…This study is expected to help in understanding the emergence of complications at a relatively early age. It is known that diagnosis of diabetes takes place in India quite late in the disease cycle and that the complications of diabetes in Indians appear a decade earlier than in people with diabetes in the West . The literature from population‐based studies in India indicate that disease diagnosis remains undetected in about half of the population with diabetes and may support the observation of a large majority of people having complications at the time of diagnosis itself .…”
Section: Discussionmentioning
confidence: 99%
“…This study is expected to help in understanding the emergence of complications at a relatively early age. It is known that diagnosis of diabetes takes place in India quite late in the disease cycle and that the complications of diabetes in Indians appear a decade earlier than in people with diabetes in the West . The literature from population‐based studies in India indicate that disease diagnosis remains undetected in about half of the population with diabetes and may support the observation of a large majority of people having complications at the time of diagnosis itself .…”
Section: Discussionmentioning
confidence: 99%
“…In a Pan-India study, only 43.4% patients had their BP checked at the time of diagnosis; the figures were 17.6%, 5.6% and 4.2% for eye examination, kidney function tests and lipid tests, respectively, for diabetics with complications [47]. At the facility level, there is a lack of timely supply of drugs and medical equipment including diagnostic kits, lack of trained providers such as medical officers, pharmacists and laboratory technicians [47]. A study found that only 10-12% of people with diabetes received modern pharmacological treatment in India on an average.…”
Section: Gaps In Facility Readiness and Provider Capabilitymentioning
confidence: 98%
“…The availability of key oral anti-diabetic drugs such as Glibenclamide varied from 100% in the state of Karnataka to 3.8% in West Bengal. Although insulin therapy is accepted as one of the most effective and dependable treatment options, barriers to its use were identified [47]; In most patients, insulin was delayed until it was absolutely necessary or when the HbA1c levels had deteriorated further to approximately 9%. Inadequate use of patient medical records and improper adherence to standard treatment protocols affect clinical decision-making; only six of the 15 health facilities in an urban health study had a system that tracked medical records of diabetes patients and providers in all these facilities expressed that there was no such thing called standard treatment protocols and treatment depends upon the individual analysis of patient condition [48].…”
Section: Gaps In Facility Readiness and Provider Capabilitymentioning
confidence: 99%
“…It includes hospital expense, laboratory expense, and cost of medications as the direct cost. 3 It was postulated that the total annual cost of diabetes care in India was INR 1230 to 1837.3 billion in 2010. 4…”
Section: Financial Burden and Diabetes-related Healthcare Costmentioning
confidence: 99%